A Digital Voice from the Dust: The Joseph Smith Papers at the Intersection of Public and Digital History1. Issue 4 (December 2016) - Rogers, Brent M.
Like other documentary editing projects, the Joseph Smith Papers—an effort to produce a comprehensive edition of the papers of Joseph Smith, the founder of the Church of Jesus Christ of Latter-day Saints, more commonly known as Mormons—seeks to provide reliable access to "the authentic voice" of its eponymous historical figure in innovative ways. As a digital voice from the dust, the project makes Smith's words, character, and context accessible in the online representation of his papers in ways that forcefully illustrate the convergence of public and digital history. This article uses the Joseph Smith Papers Project (JSPP) as a case study to look at documentary collections at the intersection of digital and public history while exploring issues of scholarship, access, and transparency. The trends described here promise to have implications for the larger fields of digitally presented public history and documentary collections.